Studi Literatur: Pentingnya Berpikir Komputasional dalam Meningkatkan Kemampuan Pemecahan Masalah Matematis Peserta Didik - Fatma Liana Rahma P; Indah Aditya Putri; Mila Sari Tanjung; Rosliana Siregar (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Computational Thinking is a way of thinking that refers to the ability to solve problems using concepts used in computing. Computational thinking is a way of thinking in solving problems that students must develop in the digital era. This research aims to examine the importance of computational thinking in improving students' mathematical problem solving abilities. The type of research used is qualitative research using a literature study approach in the form of books, notes, journals, reports of relevant research results, as well as the results of observations. The results of the analysis show that it is very important for students to have computational thinking in order to improve their mathematical problem solving abilities. Computational thinking involves solving problems using a logical and systematic mindset that involves selecting and using algorithms, data representation, problem decomposition, abstraction, pattern recognition and hypothesis testing. Computational thinking has become an important and essential skill for humans in the 21st century. Educators must advocate the importance of integrating learning with computational thinking concepts into the educational curriculum. Computational thinking has an important role in learning. This can be useful for improving mathematical problem solving abilities. Apart from that, computational thinking can also develop critical, creative and analytical thinking skills in solving complex problems, both in the context of computing and everyday life.